Strategi Komunikasi Pemasaran PT. Lakone Serasa Juara melalui Sosial Media Instagram dalam Menciptakan Brand Awareness - Hernanda, Izzul Shafira Fitri; Candrasari, Yuli (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the marketing communication strategy of PT. Lakone Serasa Champion on Instagram to increase brand awareness. This research is included in qualitative research, which is an important effort related to asking questions, through procedures, collecting specific data from informants. The circular model of some theory related to share, optimize, manage, and engage is used as an analytical theory. This research found that (1) PT. Lakone Serasa Juara uses a communication strategy through the use of advertising features on its social media. Using advertising features and paying a fee on each social media platform will have an effect on product recognition and sales; (2) PT. Lakone holds an annual event and also discounts for the winners; and (3) communication strategy through uploading photos and videos on online media by uploading photos and images in real pictures and of course having good image quality will attract consumers' interest in buying.